Transcriptomic, Proteomic and Metabolomic Analysis of Flavonoid Biosynthesis During Fruit Maturation in Rubus chingii Hu - Li, Xiaobai; Jiang, Jingyong; Chen, Zhen; Jackson, Aaron (Frontiers in Plant Science, 2021)
Rubus chingii HU, is a medicinal and nutritious fruit, which is very rich in flavonoids. However, the biosynthesis of its flavonoids is poorly understood. This study examined flavonoids and the genes/proteins at four fruit ripening phases using LC-MS/MS and qPCR. Six major kinds of anthocyanins, primarily consisted of flavanol-anthocyanins, which differed in form or concentration from other Rubus species. In contrast to other known raspberries species, R. chingii had a decline in flavonoids during fruit ripening, which was due to down-regulation of genes and proteins involved in phenylpropanoid and flavonoid biosynthesis. Unexpectedly, anthocyanin also continuously decreased during fruit maturation. This suggests that anthocyanins are not responsible for the fruit’s reddish coloration. Flavanol-anthocyanins were derived from the proanthocyanidin pathway, which consumed two flavonoid units both produced through the same upstream pathway. Their presence indicates a reduction in the potential biosynthesis of anthocyanin production. Also, the constantly low expression of RchANS gene resulted in low levels of anthocyanin biosynthesis. The lack of RchF3’5’H gene/protein hindered the production of delphinidin glycosides. Flavonoids primarily comprising of quercetin/kaempferol-glycosides were predominately located at fruit epidermal-hair and placentae. The proportion of receptacle/drupelets changes with the maturity of the fruit and, may be related to a decrease in the content of flavonoids per unit mass as the fruit matures. The profile and biosynthesis of R. chingii flavonoids are unique to Rubus. The unique flavonol pathways of R. chingii could be used to broaden the genetic diversity of raspberry cultivars and to improve their fruit quality.